Aplikasi Perangkat Bergerak Untuk Pencarian Tempat Parkir di Lingkungan Kampus Universitas Brawijaya - Adi Cahya Hermawan; Agi Putra Kharisma; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Parking lot is one of many facilities owned by all faculties in Brawijaya University. But, usually the available parking space is full at certain times. So, the students usually have to search for the empty parking slots by them selves. Currently in Universitas Brawijaya there is no application that can provide information about the parking lot that still has empty space. This research aims to make a mobile device application to provide recommendation of parking lot which still have empty space. This application uses longitude and Latitude of Google API fiture and tested using blackbox method. From the validation tests performed, the features in the application work well with a 100% percentage. Beside validation testing, there also performed quisionaire tests and field tests which results are considered as good. For each question, there is 20% rate for very good, 60% for good, and 20% for fair on average. This application can be used to help users, both students and parking officers to conduct business processes in the parking lot of Universitas Brawijaya.